Mass spectrometry for the identification and analysis of highly complex glycosylation of therapeutic or pathogenic proteins. (2nd April 2020) - Ohyama, Yukako; Nakajima, Kazuki; Renfrow, Matthew B.; Novak, Jan; Takahashi, Kazuo
ABSTRACT: Introduction: Protein glycosylation influences characteristics such as folding, stability, protein interactions, and solubility. Therefore, glycan moieties of therapeutic proteins and proteins that are likely associated with disease pathogenesis should be analyzed in-depth, including glycan heterogeneity and modification sites. Recent advances in analytical methods and instrumentation have enabled comprehensive characterization of highly complex glycosylated proteins. Area covered: The following aspects should be considered when analyzing glycosylated proteins: sample preparation, chromatographic separation, mass spectrometry (MS) and fragmentation methods, and bioinformatics, such as software solutions for data analyses. Notably, analysis of glycoproteins with heavily sialylated glycans or multiple glycosylation sites requires special considerations. Here, we discuss recent methodological advances in MS that provide detailed characterization of heterogeneous glycoproteins. Expert opinion: As characterization of complex glycosylated proteins is still analytically challenging, the function or pathophysiological significance of these proteins is not fully understood. To reproducibly produce desired forms of therapeutic glycoproteins or to fully elucidate disease-specific patterns of protein glycosylation, a highly reproducible and robust analytical platform(s) should be established. In addition to advances in MS instrumentation, optimization of analytical and bioinformatics methods and utilization of glycoprotein/glycopeptide standards is desirable. Ultimately, we envision that an automated high-throughput MS analysis will provide additional power to clinical studies and precision medicine.